Pelvic infection caused by periodontitis: A case report - Cuihong Tian; Hongle Yan; Ping Tang; Jinqiu Shi; Maolian Liang; Yanyan Wan; Weiping Li; Xizhuo Sun; Chenglu Qin (Elsevier, 2023)
Oral bacteria in patients with periodontitis can disseminate into the bloodstream via broken oral epithelial cells, causing odontogenic maxillofacial infections, brain abscesses and endocarditis. However, pelvic infection caused by periodontitis is rare. The case of a 48-year-old woman with a long history of recurrent periodontal infections, who complained of abdominal distention and pain for 14 days after dental implantation, is reported here. Pelvic ultrasound and magnetic resonance imaging signaled multiple inflammatory encapsulated effusions in the posterior uterus, which were removed by laparoscopic surgery and tested with metagenomic next-generation sequencing (mNGS). Through mNGS, numerous oral pathogens, including Filifactor alocis, were identified in the pelvic effusions. The patient was subsequently diagnosed with a pelvic infection originating from periodontitis, and recovered after undergoing surgery and targeted antibacterial treatment. Thus, the possibility of extrabuccal complications in patients with a history of periodontitis or invasive oral procedures merits closer attention.